Factors Affecting New Normal Behaviour and the Interests in Creative Tourism of South Asian Region Among Thai Tourists - Chatratichart, Waraporn; Songsiengchai, Luxsnai (Journal of Management Science Chiangrai Rajabhat University, 2023)
This research paper aims to investigate the factors affecting ‘New Normal’ behaviour and the interests in creative tourism in the South Asian region among Thai tourists. A quantitative method was adopted. The online survey research with one-shot descriptive study was implemented to collect data from two groups of individuals, according to their prior travelling experience, who either have been to countries in South Asia, or have never been to South Asia, but intend to visit countries in South Asia in the next 5 years. In total, 391 responses were received and considered valid for analysis. The findings revealed that characteristics of destination and service-related factors were the most important considerations, whereas social factors were the least important considerations in the opinions of Thai tourists, regardless of the traveling experience. Furthermore, it was found that the interest in creative tourism between two identified groups of tourists, was different in five activities with the significant level of .05. To create opportunities for creative tourism in the South Asian region among Thai tourists, suggestions have been included: to design communication campaigns according to the travelling experience; to attract experienced tourists with new routes and experiences from creative tourism; and to attract inexperienced tourists with memorable and ‘Instagrammable’ experiences.